Quality of the bicycle transportation service in small and intermediate cities in Colombia - Pacheco-García, Eduardo Alfonso; Sánchez-Delgado, Alba Yajaira (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Nowadays, the bicycle, as a means of mobility, is the most eco-friendly vehicle; however, and despite its many benefits, its use at a global scale is quite low. This study aimed to discover the reasons for the low use of bicycles as means of transportation in Colombian, by formulating a method to analyze the service quality of the Bicycle Transportation System (BTS) in small and intermediate cities of the country. Measurement techniques used in the Social Sciences allowed us to study the perception that the user has of the BTS, to identify the most representative attributes of the system and their respective variables, as well as to qualify and quantify them. Applying the method to a case city allowed elucidating the deficiencies perceived by the BTS users, as well as evaluating variables quantitative and qualitatively to obtain a level of service that measures the user acceptance rate of the BTS. The results derived from this method make possible to manage operational actions that improve efficiency in bicycle mobility, with its corresponding economic, environmental and social benefits, to ultimately improve the quality of life of its users. The method and the recommended techniques can be applied to small and intermediate cities, allowing the necessary adjustments for any other type of city.